The role of responsive mediation in the development of a novice English teacher’s understanding of the teaching of listening / O papel da mediação responsiva no desenvolvimento do ensino de compreensão oral de uma professora de inglês em início de carreira (Revista de Estudos da Linguagem, 2020)
Abstract: when adopting a Vygotskian approach to teacher education, it is believed that social interaction between an experienced teacher and a novice one has the potential to propel teacher development as the former provides mediation that is responsive to the latter’s current needs. With this in mind, the present study is aimed at investigating how a novice English as a foreign language teacher develops her understanding regarding the teaching of listening as she is mediated by a more experienced other who uses the teacher’s manual suggestions as a starting point to inquire into her practice. To do so, the study counted on nine classroom observations which were followed by interviews in which a more experienced peer mediated the teacher towards a better understanding of her teaching, using the teacher’s manual to elucidate the pedagogical concepts behind the textbook activities. Results indicate that responsive mediation provided to the teacher led her to revisit her practice, imbue it with meaning, and consequently (re)conceptualize it as the teacher’s professional activity seemed to have become closer to a communicative one – in consonance to the teacher’s manual suggestions – both her actions and justifications reverberating the moments of interaction with the more experienced teacher. In short, the study illustrates how interaction with a more experienced peer may potentially allow teachers to (re)conceptualize their teaching and, consequently, develop in the profession.Keywords: social interaction; responsive mediation; teacher development; teaching listening.Resumo: uma abordagem Vigotskiana à formação de professores concebe a interação social entre um par experiente e um professor em início de carreira como um elemento que pode potencializar o desenvolvimento deste profissional, o caráter responsivo da mediação às necessidades do professor sendo um elemento chave no processo. Dito isso, o presente estudo visa investigar como uma professora de inglês como língua estrangeira em início de carreira desenvolve seu entendimento em relação ao ensino de compreensão oral ao ser mediada por um professor mais experiente que parte das sugestões do manual do professor para mediá-la. A professora teve nove de suas aulas observadas, seguidas de entrevistas nas quais um professor mais experiente a mediou – ao usar o manual do professor para elucidar os conceitos pedagógicos que regem as atividades do livro-texto – a caminho de um melhor entendimento de sua atividade profissional. Os resultados indicam que a mediação responsiva levou a professora a revisitar sua prática, atribuir significado a ela e, consequentemente, (re)conceituá-la ao passo que as aulas pareceram aproximar-se de uma abordagem comunicativa ao ensino de línguas – indo ao encontro das sugestões do manual – sendo que suas ações e justificativas reverberaram os momentos de interação com o professor mais experiente. Por fim, o estudo ilustra como a interação com um par mais experiente tem o potencial de levar professores a (re)conceituar sua prática, consequentemente impulsionando seu desenvolvimento profissional.   Palavras-chave: interação social; mediação responsiva; desenvolvimento docente; ensino de compreensão oral.